Metode Validasi Golongan Obat Beta Blocker dalam Plasma Darah Manusia Menggunakan Metode HPLC - Andien Ravelliani; Hasna Nisrina; Lala Komala Sari; Marisah Marisah; Riani Riani; Annastya Eka Agustin; Faizal Auladi Rivianto (Publikasi Indonesia, 2022)
Bisoprolol and atenolol are beta blockers that selectively act on 1 receptors in the heart. This drug is used for the treatment of hypertension. Hypertension is an event where there is an abnormal increase in blood pressure in the arteries on a continuous basis. The normal range for blood pressure is 120/80 mmHg. The writing of this review article reviews the effect of antihypertensive drug compounds in biological samples, namely on human blood plasma using HPLC methods. Based on the results of several journals that have been reviewed, it was concluded that the drug compounds bisoprolol and atenolol in human blood plasma obtained accurate results through these two instruments.